Increased pro-inflammatory cytokines, glial activation and oxidative stress in the hippocampus after short-term bilateral adrenalectomy. Issue 1 (December 2016) - Hamadi, Naserddine; Sheikh, Azimullah; Madjid, Nather; Lubbad, Loai; Amir, Naheed; Shehab, Safa; Khelifi-Touhami, Fatima; Adem, Abdu
Abstract Background Bilateral adrenalectomy has been shown to damage the hippocampal neurons. Although the effects of long-term adrenalectomy have been studied extensively there are few publications on the effects of short-term adrenalectomy. In the present study we aimed to investigate the effects of short-term bilateral adrenalectomy on the levels of pro-inflammatory cytokines IL-1β, IL-6 and TNF-α; the response of microglia and astrocytes to neuronal cell death as well as oxidative stress markers GSH, SOD and MDA over the course of time (4 h, 24 h, 3 days, 1 week and 2 weeks) in the hippocampus of Wistar rats. Results Our results showed a transient significant elevation of pro-inflammatory cytokines IL-1β and IL-6 from 4 h to 3 days in the adrenalectomized compared to sham operated rats. After 1 week, the elevation of both cytokines returns to the sham levels. Surprisingly, TNF-α levels were significantly elevated at 4 h only in adrenalectomized compared to sham operated rats. The occurrence of neuronal cell death in the hippocampus following adrenalectomy was confirmed by Fluoro-Jade B staining. Our results showed a time dependent increase in degenerated neurons in the dorsal blade of the dentate gyrus from 3 days to 2 weeks after adrenalectomy. Our results revealed an early activation of microglia on day three whereas activation of astroglia in the hippocampus was observed at 1 week postoperatively. A progression of microglia and astroglia activation all over the dentate gyrus and their appearance for the first time in CA3 of adrenalectomized rats hippocampi compared to sham operated was seen after 2 weeks of surgery. Quantitative analysis revealed a significant increase in the number of microglia (3, 7 and 14 days) and astrocytes (7 and 14 days) of ADX compared to sham operated rats. Our study revealed no major signs of oxidative stress until 2 weeks after adrenalectomy when a significant decrease of GSH levels and SOD activity as well as an increase in MDA levels were found in adrenalectomized compared to sham rats. Conclusion Our study showed an early increase in the pro-inflammatory cytokines followed by neurodegeneration and activation of glial cells as well as oxidative stress. Taking these findings together it could be speculated that the early inflammatory components might contribute to the initiation of the biological cascade responsible for subsequent neuronal death in the current neurodegenerative animal model. These findings suggest that inflammatory mechanisms precede neurodegeneration and glial activation.